Symplectic and Contact Geometry with Complex Manifolds - Nazimuddin, AKM; Ali, Md Showkat (GANIT: Journal of Bangladesh Mathematical Society, 2019)
In this paper, we discuss about almost complex structures and complex structures on Riemannian manifolds, symplectic manifolds and contact manifolds. We have also shown a special comparison between complex symplectic geometry and complex contact geometry. Also, the existence of a complex submanifold of n-dimensional complex manifold which intersects a real submanifold GANIT J. Bangladesh Math. Soc.Vol. 39 (2019) 119-126